Targeted muscle reinnervation - Kuiken, Todd A.; Feuser, Aimee E. Schultz; Barlow, Ann K. (Boca Raton : Taylor & Francis, 2014)
"This reference covers clinical and bioengineering aspects of muscle reinnervation, a popular new technique at the boundary of biomedical and rehabilitation engineering and neuroscience. With contributions from pioneers in the field, the book provides a review of muscle reinnervation from a biomedical engineering and clinical perspective. It describes neuroscience and other related neuroprosthetic techniques. A companion website offers a wide range of videos and multimedia material to aid in comprehension and application"--Provided by publisher.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nervous system -- Regeneration; Arm -- Innervation; Amputees -- Rehabilitation; Artificial limbs; Electronic books